Penerapan Metode Market Basket Analysis Pada Situs Web E-Commerce (Studi Kasus: Dhian Handicraft Indonesia) - Gemala, Medina; Arifin, Mochammad; Aliffianto, Ahmad Yanu (Jurnal JSIKA, 2012)
In an effort to increase the volume of sales of a product in an e-commerce, the comfort level of service to customers is one of the factors that are important and need to be considered by the management. So, management must make a practical step by approaching the customer to be aware of how the behavior of customers in the deal. In this final project regarding creation of personalization systems on web sites that are used to determine the pattern of customer transactions. This system is expected to assist the management in managing the customers  catalog layout , so the comfort level of customers satisfied because the system seems to know their customers better. Naturally, the sale of a product will increase because customers feel pampered. This final testing of the customer transaction data e-commerce web sites were calculated using Market Basket Analysis, which is one of data mining techniques are used to determine the minimum support and minimum confidence is entered by the management to later mining process so as to generate association rules from customer transaction data. Association rules generated are used to build a personalized system for customers and can be considered for the management to set the location of product catalogs in e-commerce website and inform them of any unusual items customers purchased through the transaction history. The conclusion of this thesis is to produce information on items purchased together in the sales process on Dhian Handicraft Indonesia to adjustment of a model for future sales. Keyword: Kata kunci : data mining, e-commerce, Market Basket Analysis.